REPORT OF THE PRESIDENT. - White, John Arch (The Accounting Review, 1957)
The article presents a report from the President of American Institute of Accountants. The annual convention of the Association was held on the campus of the University of Washington, Seattle. The prestige of the Association rests heavily on "The Accounting Review." This quarterly is generally recognized as one of the best publications in accountancy. One of the major objectives of the Association is the promotion of research. One of the features of the annual convention in recent years has been the presentation of the Alpha Kappa Psi Award. Due to the continuing growth of the Association and the increasing burden of work on the Executive Committee, it was decided that an additional vice-president would facilitate the operations of the Association. At the annual meeting in Seattle, Washington, a special committee report adding a fourth vice-president to the Executive Committee was approved. This expansion in the membership of the Executive Committee will be made at the next annual election.